Bevarande av naturvärdesträd i enlighet med FSC och Holmen Skogs naturvårdspolicy - Gålnander, Helena (2006)
In the end of 1998 the company Holmen Skog AB was certified accordint to the FSC system with an area of 1 036 000 hectare. After that Holmen Skog AB has been working actively with the nature conservation in the forestry. In order to control the quality of the company's nature conservation in final fellings they started a yearly inventory which is called BAKRUS (Judgement of ecological and culture care in relations to policies for a persevering silviculture). After 1999 the control was expended to include all actions in the forest. The collected data is the basis for the evaluation of how the regions and districts attain the company's strategic objective for nature conservations. The strategic objective is that at least 90 % of the final felled areas only haves one deviation per area. No deviation is tolerated concerning watercourse, relic of antiquity, areas with high environmental value and obvious green tree retention.